2014
DOI: 10.1080/09658211.2014.884138
|View full text |Cite|
|
Sign up to set email alerts
|

A pancultural perspective on the fading affect bias in autobiographical memory

Abstract: The Fading Affect Bias (FAB) refers to the negative affect associated with autobiographical events fading faster than the positive affect associated with such events, a reliable and valid valence effect established by researchers in the U.S.A. The present study examined the idea that the FAB is a ubiquitous emotion regulating phenomenon in autobiographical memory that is present in people from a variety of cultures. We tested for evidence of the FAB by sampling more than 2,400 autobiographical event descriptio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
79
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(88 citation statements)
references
References 43 publications
5
79
0
4
Order By: Relevance
“…In addition, the FAB was positively related to spirituality, which is positively related to positive mental health outcomes (Cohen, 2002;Ellison & Fan, 2007;Kim et al, 2004;Underwood & Teresi, 2002). Together, these results extend the literature on the FAB to the context of religion, and they support the claim that the FAB is a healthy coping mechanism at a general level (Ritchie et al, 2014a;.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…In addition, the FAB was positively related to spirituality, which is positively related to positive mental health outcomes (Cohen, 2002;Ellison & Fan, 2007;Kim et al, 2004;Underwood & Teresi, 2002). Together, these results extend the literature on the FAB to the context of religion, and they support the claim that the FAB is a healthy coping mechanism at a general level (Ritchie et al, 2014a;.…”
Section: Discussionsupporting
confidence: 66%
“…Whereas the literature supports the FAB as a healthy coping mechanism at a general level, two studies examining individual differences and related events have found that the FAB predicts outcomes that can either enhance healthy or unhealthy outcomes. As religious studies have shown that religious variables are related to positive outcomes, and Ritchie et al (2014a) encouraged researchers to examine additional moderators and mediators of the FAB, we wanted to give the FAB a favorable chance to be a healthy coping mechanism at both the general and specific levels of analysis by testing it in the context of religion.…”
Section: The Current Studymentioning
confidence: 99%
“…Although Ritchie et al (2014) found a fading effect bias in samples from six countries, these were mostly Western. Furthermore, the functions of autobiographical memory differ according to the valence of the memory: negative memories often have a directive function, whereas positive memories are more likely to cover self-and social functions (Rasmussen & Berntsen, 2009).…”
Section: Event Centrality For Negative Events Across Culturesmentioning
confidence: 93%
“…Less clear and vivid images, which indicate more distant objects, also evoke weaker emotion (De Cesarei & Codispoti, 2008). Moreover, emotion associated with an autobiographical memory becomes less intense with general passage of time (e.g., prolonged temporal distance and increased memory age) in a biased tendency such that negative emotion fades faster than positive emotion does (i.e., fading affect bias, e.g., Ritchie et al, 2015). The principle of how emotional intensity changes according to objective distance (e.g., physical or temporal distance) can be applied to self-rated psychological distance.…”
Section: Introductionmentioning
confidence: 97%